Analysis of Students' Errors Based on Newman's Errors in Solving Mathematical Reasoning Problems - Redy Williantama Zulhafendi; Yerizon Yerizon; Fitrani Dwina; Shinta Sari (Department of Mathematics, Universitas Negeri Padang (UNP), 2026)
Mathematical reasoning is one of the essential competencies that students must possess to face the challenges of 21st-century learning. However, many students still struggle to solve problems that assess their mathematical reasoning. This study aims to analyse the types of errors students make using Newman’s Error Analysis procedure. The research employed a descriptive qualitative method, with 37 twelfth-grade high school students selected through purposive sampling. Data were collected through a mathematical reasoning ability test and interviews. The quantitative data from the test were analysed descriptively to identify error patterns, while the qualitative data from interviews were analysed thematically through data reduction, data display, and conclusion drawing. Most students made errors in three main stages, namely understanding the problem concept, transforming verbal information into appropriate mathematical representations, and applying mathematical procedures or algorithms correctly. Furthermore, the analysis showed that conceptual misunderstanding was the most prevalent type of error, often leading to subsequent transformation and process-skill errors. These findings suggest that teachers need to design learning interventions that strengthen conceptual comprehension and develop students’ systematic problem-solving strategies.